A Haptic System for Switching Wind Temperatures Based on Ultrasonic Vibrations, Peltier Elements, and Electrical Resistances for Multisensory Applications - Rodrigues, Eduardo C.; Saleme, Estêvão B.; Santos, Celso A. S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2021: Proceedings of the 27th Brazilian Symposium on Multimedia and the Web, 2021)
Adding sensory effects to applications has proven to increase users' quality of experience (QoE). As immersive technologies advance in the fields of entertainment, education, training, and so forth, more fine-grained functions are craved by users to have truly captivating and (nearly) realistic experiences. These new functions, in turn, push forward both the industry and academia on developing solutions to overcome the current limitations. This is indeed the particular case of multimedia systems enriched with thermal wind sensations. Whilst both wind and thermal effects have been included separately in such systems, the lack of wind at a low or high temperature has been noticed by users. It is not trivial building, controlling, and working with devices at different temperatures hit by wind at the same time. This is exacerbated by the fact that different technologies are used to this end. In this paper, we introduce a haptic system that allows the creation and delivery of hot and cold airflow synchronised with audiovisual content. The system combines the vaporisation of cooled water by Peltier plates for cold wind and hair dryers for warm wind steered by wind fans. To assess our system, we analysed the time our devices take to deliver these effects considering different starting temperatures in the environment. Furthermore, we annotated three videos with hot wind, cold wind, and both effects respectively to observe the feasibility of having those effects integrated with audiovisual content. Our findings suggest recommendations for the appropriate triggering of these types of sensory effects combined with multimedia content taking into account our setup.